The Effect of Financial Literacy, Risk Perception, and Income on Investment Decisions with Self-Efficacy as an Intervening Variable in Generation Z of GemsGBKP Binjai City - Kristiani Br Ginting; Noni Ardian; Ramadhan Harahap (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of financial literacy, risk perception, and income on investment decisions with self-efficacy as an intervening variable in Generation Z of GBKP Gem Binjai City. This type of research is quantitative with a causal approach using a survey method. The research population is all members of Generation Z of Permata GBKP Binjai City which totals 250 people, with a sample of 71 respondents using the Slovin formula and simple random sampling techniques. Data was collected through a questionnaire with a Likert scale and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results of the study show that financial literacy, income, and risk perception do not have a significant direct effect on investment decisions. However, these three variables have a positive and significant effect on self-efficacy, with income having the strongest influence, followed by risk perception and financial literacy. Self-efficacy has been shown to have a positive and significant effect on investment decisions, and plays a role as a full mediator in the relationship between financial literacy and income on investment decisions. The research model has good predictive ability with moderate categories for investment decisions and self-efficacy, and shows excellent predictive relevance.